Correlation of Body Age with anthropometric parameters in students (Journal of Basic and Applied Research in Biomedicine, 2022)
Obesity is becoming a pandemic these days. People are overweight and are losing the joy of self control. Lack of exercise, poor dietary habits lead to hypertension and diabetes mellitus. It is essential to make students aware of their faulty habits so they may correct it at an early age. We analyzed the BMI, Body age, Visceral Fat, Total and subcutaneous fat using an OMRON Machine by bioelectrical impedance for 52 students. About 60% of students whose body age was more than their actual age were counseled to eat rightly and exercise regularly.